Determinación de la calidad del agua del río Jubones en la Parroquia La Iberia por medio de parámetros físico químicos - Rivas Echeverría, Viviana R. (2005)
The present investigation work one carries out for not having data on this topic and with the purpose that the results are employees in programs of environmental impact. For the present investigation they took samples in the river Jerkins in the Parish the Iberia taking into accounts the basic conditions for sampling.